(5zy)(-4z)=

Simple and best practice solution for (5zy)(-4z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5zy)(-4z)= equation:


Simplifying
(5zy)(-4z) = 0

Remove parenthesis around (5yz)
5yz(-4z) = 0

Remove parenthesis around (-4z)
5yz * -4z = 0

Reorder the terms for easier multiplication:
5 * -4yz * z = 0

Multiply 5 * -4
-20yz * z = 0

Multiply yz * z
-20yz2 = 0

Solving
-20yz2 = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-20'.
yz2 = 0.0

Simplifying
yz2 = 0.0

The solution to this equation could not be determined.

See similar equations:

| 32+3x=36 | | 9p-4=77 | | 4x^2+16x=24 | | -5n+1-2n+n-4=5 | | 5x+9+3y+8=180 | | y^2+8y+11=0 | | 4w-7=17 | | 200=7(5-4b)-5b | | 5x+4(4x+8)=10 | | 5x+9+3y+8=108 | | -3n-8(1+7)=-8 | | 6(6-w)+3=-3(w-3)-11 | | 19-(-18)-(-14)= | | t*2t=0 | | 22+2x=0.5 | | X-3(-3x+12)=14 | | F(x)=2x^3-10x^2-8x-40 | | 10s-13=8s-10 | | 8k+5=77 | | 1/2n-16 | | s(2)fors(t)=t^2-3t+1 | | 3x=3/7*7/3 | | 46-3x=10-7x | | -6r-4(5r+9)=12-10r | | d/dx(4e^x)cos(x) | | 4x-4(5x-4)=16 | | 5x-4-3x=-32 | | 7p+4=11 | | N-(-6)=56 | | 1/10=4/5 | | 5+x-14=2x-7 | | 5x-4-3x=32 |

Equations solver categories